<h2>
Answer with explanation:</h2>
We know that the average rate of function f(x) from x=a to x=b i.e. in the interval [a,b] is calculated as follows:
![Rate\ of\ change=\dfrac{f(b)-f(a)}{b-a}](https://tex.z-dn.net/?f=Rate%5C%20of%5C%20change%3D%5Cdfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D)
a)
![f(x)=x^2+3x](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2%2B3x)
interval: [-2,3]
We have:
![f(3)=3^2+3\times 3\\\\\\f(3)=9+9\\\\f(3)=18](https://tex.z-dn.net/?f=f%283%29%3D3%5E2%2B3%5Ctimes%203%5C%5C%5C%5C%5C%5Cf%283%29%3D9%2B9%5C%5C%5C%5Cf%283%29%3D18)
and
![f(-2)=(-2)^2+3\times (-2)\\\\\\f(-2)=4-6\\\\\\f(-2)=-2](https://tex.z-dn.net/?f=f%28-2%29%3D%28-2%29%5E2%2B3%5Ctimes%20%28-2%29%5C%5C%5C%5C%5C%5Cf%28-2%29%3D4-6%5C%5C%5C%5C%5C%5Cf%28-2%29%3D-2)
The average rate of change is calculated as:
![=\dfrac{f(3)-f(-2)}{3-(-2)}\\\\\\=\dfrac{18-(-2)}{5}\\\\\\=\dfrac{20}{5}\\\\\\=4](https://tex.z-dn.net/?f=%3D%5Cdfrac%7Bf%283%29-f%28-2%29%7D%7B3-%28-2%29%7D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B18-%28-2%29%7D%7B5%7D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B20%7D%7B5%7D%5C%5C%5C%5C%5C%5C%3D4)
Hence, Average rate of change is: 4
b)
![f(x)=3x-8](https://tex.z-dn.net/?f=f%28x%29%3D3x-8)
interval: [4,5]
![f(5)=3\times 5-8\\\\\\f(5)=15-8\\\\\\f(5)=7](https://tex.z-dn.net/?f=f%285%29%3D3%5Ctimes%205-8%5C%5C%5C%5C%5C%5Cf%285%29%3D15-8%5C%5C%5C%5C%5C%5Cf%285%29%3D7)
and
![f(4)=3\times 4-8\\\\\\f(4)=12-8\\\\\\f(4)=4](https://tex.z-dn.net/?f=f%284%29%3D3%5Ctimes%204-8%5C%5C%5C%5C%5C%5Cf%284%29%3D12-8%5C%5C%5C%5C%5C%5Cf%284%29%3D4)
The average rate of change is calculated as:
![=\dfrac{f(5)-f(4)}{5-4}\\\\\\=\dfrac{7-4}{1}\\\\\\=3](https://tex.z-dn.net/?f=%3D%5Cdfrac%7Bf%285%29-f%284%29%7D%7B5-4%7D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B7-4%7D%7B1%7D%5C%5C%5C%5C%5C%5C%3D3)
Hence, Average rate of change is: 3
c)
![f(x)=x^2-2x](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2-2x)
interval : [-3,4]
![f(4)=4^2-2\times 4\\\\\\f(4)=16-8\\\\\\f(4)=8](https://tex.z-dn.net/?f=f%284%29%3D4%5E2-2%5Ctimes%204%5C%5C%5C%5C%5C%5Cf%284%29%3D16-8%5C%5C%5C%5C%5C%5Cf%284%29%3D8)
![f(-3)=(-3)^2-2\times (-3)\\\\\\f(-3)=9+6\\\\\\f(-3)=15](https://tex.z-dn.net/?f=f%28-3%29%3D%28-3%29%5E2-2%5Ctimes%20%28-3%29%5C%5C%5C%5C%5C%5Cf%28-3%29%3D9%2B6%5C%5C%5C%5C%5C%5Cf%28-3%29%3D15)
The average rate of change is calculated as:
![=\dfrac{f(4)-f(-3)}{4-(-3)}\\\\\\=\dfrac{8-15}{7}\\\\\\=\dfrac{-7}{7}=-1](https://tex.z-dn.net/?f=%3D%5Cdfrac%7Bf%284%29-f%28-3%29%7D%7B4-%28-3%29%7D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B8-15%7D%7B7%7D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B-7%7D%7B7%7D%3D-1)
Hence, Average rate of change is: -1
d)
![f(x)=x^2-5](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2-5)
interval : [-1,1]
![f(1)=1-5\\\\f(1)=-4](https://tex.z-dn.net/?f=f%281%29%3D1-5%5C%5C%5C%5Cf%281%29%3D-4)
and
![f(-1)=(-1)^2-5\\\\\\f(-1)=1-5\\\\\\f(-1)=-4](https://tex.z-dn.net/?f=f%28-1%29%3D%28-1%29%5E2-5%5C%5C%5C%5C%5C%5Cf%28-1%29%3D1-5%5C%5C%5C%5C%5C%5Cf%28-1%29%3D-4)
The average rate of change is calculated as:
![=\dfrac{f(1)-f(-1)}{1-(-1)}\\\\\\=\dfrac{-4-(-4)}{2}\\\\\\=\dfrac{0}{2}=0](https://tex.z-dn.net/?f=%3D%5Cdfrac%7Bf%281%29-f%28-1%29%7D%7B1-%28-1%29%7D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B-4-%28-4%29%7D%7B2%7D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B0%7D%7B2%7D%3D0)
Hence, Average rate of change is: 0
<em>Hence, on arranging the functions from greatest to least value based on average rate of change in the specified interval is:</em>
![f(x)=x^2+3x](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2%2B3x%3Cf%28x%29%3D3x-8%3Cf%28x%29%3Dx%5E2-5%3Cf%28x%29%3Dx%5E2-2x)
i.e. a < b < d < c